A7.8 Autonomic dysfunction in the preclinical phase of rheumatoid arthritis. (13th February 2015) - Koopman, FA; Tang, MW; Vermeij, J; de Hair, MJ; Choi, IY; Vervoordeldonk, MJ; Gerlag, DM; Karemaker, JM; Tak, PP
Abstract : Background and objectives: Rheumatoid arthritis (RA) is accompanied by changes in the autonomic nervous system, mainly lower activity of the parasympathetic nervous system. Autonomic changes can be detected by changes in heart rate variability (HRV). RA development starts years before the first presentation of arthritis; we hypothesised that autonomic changes may be present in individuals at risk of development of arthritis. Material and methods: 10-minutes recordings of continuous blood pressure and heart rate were made in supine (resting) and upright (active) position in healthy subjects (HS, n = 20), individuals at risk of RA development (individuals at risk, n = 50) and RA patients (RA, n = 20). In addition, sympathetic proteins, (nor)epinephrine and the parasympathetic nicotinic acetylcholine receptor type 7 (α7nAChR) on monocytes were measured in venous peripheral blood samples. Resting heart rate (RHR) was also evaluated by a single, non-continuous measurement in an independent cohort of autoantibody positive individuals at risk of developing RA (n = 45). Results/Discussion: Individuals at risk had a significantly higher RHR (68 beats per minute (bpm)) compared to HS (60 bpm, p = 0.006) and similar to RA patients (68 bpm, p = 0.38), indicating lower parasympathetic activity compared to HS. Other parasympathetic HRV parameters were lower compared to HS and norepinephrine levels were higher in individuals at risk compared to HS and RA. Dichotomizing RHR in < and ≥70 bpm in the group of individuals at risk, we could demonstrate that the majority of HRV parameters were significantly lower in individuals with RHR ≥ than <70 bpm. The parasympathetic receptor α7nAChR on peripheral CD14 + monocytes was lower in individuals at risk with RHR ≥ 70 bpm than <70 bpm. In the independent cohort RHR was higher at baseline in individuals who developed arthritis (n = 14) vs. those who did not (n = 31; 73.8 vs. 65.8 bpm, p = 0.018) after follow, and this was associated with RA development in the future (hazard ratio 1.098: 95% CI 1.012–1.191, p = 0.025). Conclusions: Individuals at risk of RA development have lower parasympathetic activity compared to HS, and resemble RA patients. Increased RHR in individuals at risk is associated with RA development and a RHR ≥70 bpm measured by short-term HRV registration is accompanied by detrimental changes in all HRV parameters. These data support the notion that decreased vagus nerve tone may contribute to RA development.